Physiological fluid interfaces: Functional microenvironments, drug delivery targets, and first line of defense. (August 2021) - Bertsch, Pascal; Bergfreund, Jotam; Windhab, Erich J.; Fischer, Peter
Abstract: Fluid interfaces, i.e. the boundary layer of two liquids or a liquid and a gas, play a vital role in physiological processes as diverse as visual perception, oral health and taste, lipid metabolism, and pulmonary breathing. These fluid interfaces exhibit a complex composition, structure, and rheology tailored to their individual physiological functions. Advances in interfacial thin film techniques have facilitated the analysis of such complex interfaces under physiologically relevant conditions. This allowed new insights on the origin of their physiological functionality, how deviations may cause disease, and has revealed new therapy strategies. Furthermore, the interactions of physiological fluid interfaces with exogenous substances is crucial for understanding certain disorders and exploiting drug delivery routes to or across fluid interfaces. Here, we provide an overview on fluid interfaces with physiological relevance, namely tear films, interfacial aspects of saliva, lipid droplet digestion and storage in the cell, and the functioning of lung surfactant. We elucidate their structure-function relationship, discuss diseases associated with interfacial composition, and describe therapies and drug delivery approaches targeted at fluid interfaces. Statement of Significance: Fluid interfaces are inherent to all living organisms and play a vital role in various physiological processes. Examples are the eye tear film, saliva, lipid digestion & storage in cells, and pulmonary breathing. These fluid interfaces exhibit complex interfacial compositions and structures to meet their specific physiological function. We provide an overview on physiological fluid interfaces with a focus on interfacial phenomena. We elucidate their structure-function relationship, discuss diseases associated with interfacial composition, and describe novel therapies and drug delivery approaches targeted at fluid interfaces. This sets the scene for ocular, oral, or pulmonary surface engineering and drug delivery approaches. Graphical abstract: Image, graphical abstract